1989
DOI: 10.1209/0295-5075/9/6/005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Nuclear Photoabsorption Cross-Sections by the Modified Quasi-Deuteron Model

Abstract: Levinger's modified quasi-deuteron model has been used to analyse available experimental data on total nuclear photoabsorption cross-section in the mass range 7 ⩽ A ⩽ 238 and in the energy range (35 ÷ 140) MeV. It is shown that the measured cross-sections are successfully reproduced by the formula σT(Eγ) = LNZ/AσD(Eγ) exp [- D/E] with L = 6.1 ± 2.2 and D = 0.72A0.81.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Figure 6 shows partial photoneutron cross sections obtained in the new measurement in comparison with the TALYS [14] calculation of the giant-dipole resonance (GDR) and quasi-deuteron component [15,16]. The GDR cross section was obtained within the Hartree-Fock-Bogolyubov plus quasiparticle random phase approximation approach on the basis of the D1M Gogny interaction both for the E1 [17] and M1 [18] components.…”
Section: Bi(xn) Datamentioning
confidence: 99%
“…Figure 6 shows partial photoneutron cross sections obtained in the new measurement in comparison with the TALYS [14] calculation of the giant-dipole resonance (GDR) and quasi-deuteron component [15,16]. The GDR cross section was obtained within the Hartree-Fock-Bogolyubov plus quasiparticle random phase approximation approach on the basis of the D1M Gogny interaction both for the E1 [17] and M1 [18] components.…”
Section: Bi(xn) Datamentioning
confidence: 99%
“…In the decades following Levinger's original work there were few compilations of the photonuclear data and systematic evaluations of the Levinger constant (see e.g. [10] and references therein). It was also found that 2-body short range correlations captured so well by the quasi-deuteron model plays an important role in analyzing hard nuclear electron scattering experiments, see e.g.…”
mentioning
confidence: 99%
“…Consequently we shall concentrate on the E1 transition cross-section, which in principle can be extracted from the angular distribution of the emitted pn pair. The experimental evaluation of Levinger's constant [10] is than used to extract the proton-neutron contact.…”
mentioning
confidence: 99%
See 2 more Smart Citations